Clinical-epidemiological characteristics in patients with covid-19 diagnosis. Virú health network, march - may 2020 - Narro-Cornelio, Katherine Mariet (2021)
Objetive. To describe the clinical-epidemiological characteristics in patients with a confirmed diagnosis of COVID-19 from the Viru Health Network from March to May 2020. Material and Methods: Study with a quantitative approach and descriptive observational design with secondary data. The population made up of patients diagnosed positive for COVID-19 with molecular and serological tests. The documentation technique was applied. The established instrument, based on the COVID-19 clinical epidemiological investigation card used during the clinical consultation. Sociodemographic variables, antecedents and clinical manifestations were identified. The data was processed using dynamic tables in Excel and SPSS 26.0 software. Results: 67.7% of COVID-19 cases were found in the Virú Health Network in the adult and elderly life stages. Prevalence of male patients (57.4%) compared to female (42.6%). The Virú district presented 52.9% of the confirmed cases of patients with COVID-19. The symptoms were: cough (48.7%), general malaise (48.2%), sore throat (39.1%) and fever / chills (37.5%), nasal congestion (22.0%), headache (21.3%) respiratory distress (17.1%) ), muscle pain (12.2%) and chest pain (8.4%). Other symptoms to a lesser extent, nausea / vomiting (5.6%), diarrhea (5.2%), abdominal and joint pain (1.9%). The predominant comorbidities are: diabetes (3.7%), cardiovascular disease (3.5%), pregnancy (1.9%), chronic lung disease (0.5%), liver disease and cancer (0.2%) respectively. Conclusions: Within the clinical-epidemiological characteristics, we have that the most frequent sex was male, being cough the main symptom and diabetes mellitus the most frequent comorbidity.